2007
DOI: 10.1002/pca.973
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted extraction of the main phenolic compounds in flaxseed

Abstract: A microwave-assisted extraction (MAE) method has been applied for the first time to the extraction of the main lignan, secoisolariciresinol diglucoside (SDG), and the two most concentrated hydroxycinnamic acid glucosides in flaxseed. The effects of microwave power, extraction time and alkaline treatment were investigated. It was shown that a 3 min MAE resulted in an SDG content of 16.1+/-0.4 mg/g, a p-coumaric acid glucoside content of 3.7+/-0.2 mg/g and a ferulic acid glucoside content of 4.1+/-0.2 mg/g. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(77 citation statements)
references
References 35 publications
6
70
1
Order By: Relevance
“…In the study of Li et al (2008), SDG content was found to be 1.54% in the defatted flaxseed powder on a dry matter basis. This result is in agreement with previous findings, in which SDG content varied between 0.6 and 2.9% in the defatted flaxseed powder (JOHNSSON et al, 2002;BEEJMOHUN et al, 2007). Struijs et al (2007) obtained 7.5% of the lignan macromolecule from 400 g of flaxseed hulls indicating that flaxseed hulls were enriched in SDG compared to the cotyledons.…”
Section: Chemical Composition Of Flaxseedsupporting
confidence: 83%
“…In the study of Li et al (2008), SDG content was found to be 1.54% in the defatted flaxseed powder on a dry matter basis. This result is in agreement with previous findings, in which SDG content varied between 0.6 and 2.9% in the defatted flaxseed powder (JOHNSSON et al, 2002;BEEJMOHUN et al, 2007). Struijs et al (2007) obtained 7.5% of the lignan macromolecule from 400 g of flaxseed hulls indicating that flaxseed hulls were enriched in SDG compared to the cotyledons.…”
Section: Chemical Composition Of Flaxseedsupporting
confidence: 83%
“…Studies showed that microwaves can penetrate plant matrix directly, resulting highly localized temperature and pressure inside plant cells, which can cause selective migration of target compounds into solvent rapidly [Yan et al 2010, Upadhyay et al 2012. So far, microwave treatment has been widely employed to extract phen olics from different plant materials [Beejmohun et al 2007, Kalia et al 2008, Sutivisedsak et al 2010, Tsubaki et al 2010, Song et al 2011. To our best knowledge, usage of MAE has not been previously reported for 6-gingerol extraction in ginger.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave-assisted extraction of phenolic compounds from different plants has been studied before by different researchers (Beejmohun et al 2007;Proestos and Komaitis 2008). Gallo et al (2010) extracted phenolic compounds from four different spices, namely Cinnamomum zeylanicum, Coriandrumsativum, Cuminum cyminum, and Crocus sativus.…”
Section: Introductionmentioning
confidence: 99%